The images of alcohol and abstinence in Egyptian films: A content analysis - Khatcherian, Arpi Sarkis (AUC Knowledge Fountain, 2017)
Images of alcohol consumption, drunkenness, inebriation, and abstinence have permeated Egyptian films since the industry’s formative years. This study aimed at uncovering the extent and nature of alcoholic content in Egyptian cinema and the possible health implications of such depictions using the perspective of media-influenced perceptions of social reality and the lens of social cognitive theory. For this purpose, the study analyzed the depiction of alcohol in Egyptian films beginning in 1952 till 2015. Content analysis of a stratified random sample of 337 Egyptian films was conducted using the standardized and tested tool developed by The Annenberg-Robert Wood Johnson Coding of Health and Media Project (CHAMP). The unit of analysis was the five-minute segment which provides a uniform and easily identifiable base for comparison. Coding was preceded by a series of seven in-depth interviews with industry experts to contextualize research findings along with historical and sociopolitical changes in Egypt. A total of 1,786 five-minute segments were coded for their alcohol content with 47 films (14%) being alcohol-free. Alcohol was found to be a constant and consistent feature of Egyptian cinema across time and genres. The rate and explicitness of alcohol depiction in films was found to have decreased over the years. It was found that drinking usually occurred by the most significant characters in films and was more often by men. Brand visibility was also a regular feature especially for beers followed by spirits, raising concerns about observational mediated modeling as postulated by social cognitive theory. Moreover, the positive psychological effects of drinking were more commonly shown compared to the negative physiological consequences of alcohol consumption. It was found that less explicit and more explicit depictions of drinking were almost on par, potentially affecting popular beliefs about alcohol as postulated by the perceptions of social reality perspective.